FUNGSI KELOMPOKTANI DALAM PENERAPAN SLPTT PADI SAWAH DI KECAMATAN MEGAMENDUNG KABUPATEN BOGOR PROVINSI JAWA BARAT - Asep Harun; Nawangwulan Widyastuti; Endang Krisnawati (Politeknik Pembangunan Pertanian Bogor, 2020)
The experiment was conducted in the District of Megamendung Bogor Regency of West Java Province at March 18 until May 12 2013. This study aims to determine and quantify the extent of relationship functioning farmer groups in the PTT application of rice (Oryza sativa L.). Instruments used form questionnare distributed to 30 farmers. Research variables consist of the independent variable (x) is the function of kelompoktani, while the dependent variable (y) is the component PPT rice. Data were analyzed using Spearman rank correlation coefficient analysis. The result showed there was a significant relationship between function of group farmers as classroom learning to the application of quality seeds, legowo technique, balanced fertilization, and IPM implementation with r value 0,627; 0,610; 0,577; and 0,512 respectively. Group farmers function as cooperation showed significant relationship to the the application of quality seeds, legowo technique, balanced fertilization, and IPM implementation with r value 0,513; 0,427; 0,438; and 0,375 respectively. Group farmers function as production unit showed significant relationship to the the application of quality seeds, legowo technique, balanced fertilization, and IPM implementation with r value 0,695; 0,647; 0,673; and 0,573 respectively.